BS EN 2302. Aerospace series. Heat resisting nickel base alloy NiCr20Co3Fe3 - Rm ≥ 650 MPa. Sheets and strips, cold rolled. 0, 25 mm < a ≤ 3 mm. (16th June 2022) - British Standards Institution,
No abstract available